Trade openness and foreign direct investment: the impact of free trade agreements in Latin America - Ponce Ugolini, Aldo Fernando (2006)
This paper sheds light on the performance of Latin American governments in attracting foreign direct investment (FDI) through trade policies, specifically by signing free trade agreements with other countries. The relationship between FDI and trade for Latin America has previously been analyzed, but the relationship between the degree of «openness» (imports plus exports divided by the domestic product) and FDI has not been conclusive. At the same time, the effect of specific trade policies on FDI flows has not been extensively studied. Some state trade policies could produce a significant impact in attracting FDI. Specifically, through the implementation of a number of free trade agreements, several Latin American countries have been able to attract greater flows of foreign direct investment. The implementation of such free trade agreements formed part of a more general scheme of economic reforms launched by Latin American countries since the mid-1980s. The goals of these reforms were to adjust the region’s economies and improve their competitiveness by liberalizing trade, privatizing, and deregulating their markets. Those countries that signed more free trade agreements – or signed them with the largest economies in the world – increased their ability to attract FDI. I test the impact of this policy on the behavior of FDI flows through a panel data model for 17 Latin American countries for the period between 1985 and 2003.